2009
DOI: 10.1007/s11095-009-9932-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer, Anti-Diabetic and Other Pharmacologic and Biological Activities of Penta-Galloyl-Glucose

Abstract: Abstract1, 2, 3, 4, 6-penta-O-galloyl-β-D-glucose (PGG) is a polyphenolic compound highly enriched in a number of medicinal herbals. Several in vitro and a handful of in vivo studies have shown that PGG exhibits multiple biological activities which implicate a great potential for PGG in the therapy and prevention of several major diseases including cancer and diabetes. Chemically and functionally, PGG appears to be distinct from its constituent gallic acid or tea polyphenols. For anti-cancer activity, three pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
227
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(243 citation statements)
references
References 102 publications
10
227
0
6
Order By: Relevance
“…The in vitro antitumor activity observed could be related to the presence of trigalloyl-HHDP-glucoside, followed by pentagalloyl glucoside, the two main polyphenols detected in the flowers, belonging to the ellagitannins family, which has shown antitumor activity in vitro. Pentagalloyl glucoside can act as a proapoptotic, anti-proliferative, anti-angiogenic and anti-metastasic compound and has been used in prostate, lung, breast cancer as well as sarcoma (Zhang et al, 2009). Although the antitumor potential was not as low as ellipticine, the results were very close to the GI 50 of other natural plant extracts (Guimarães et al, 2013), and in some cases even better .…”
Section: Antitumor Activitymentioning
confidence: 81%
See 1 more Smart Citation
“…The in vitro antitumor activity observed could be related to the presence of trigalloyl-HHDP-glucoside, followed by pentagalloyl glucoside, the two main polyphenols detected in the flowers, belonging to the ellagitannins family, which has shown antitumor activity in vitro. Pentagalloyl glucoside can act as a proapoptotic, anti-proliferative, anti-angiogenic and anti-metastasic compound and has been used in prostate, lung, breast cancer as well as sarcoma (Zhang et al, 2009). Although the antitumor potential was not as low as ellipticine, the results were very close to the GI 50 of other natural plant extracts (Guimarães et al, 2013), and in some cases even better .…”
Section: Antitumor Activitymentioning
confidence: 81%
“…Although some gallotannins have displayed some in vitro antitumor and antiproliferative activities (Zhang et al, 2009), as well as effective inhibition of some bacterial pathogens (Engels et al, 2009), to the authors knowledge, this is the first report on the antitumor and antimicrobial activities of decoctions and infusions of chestnut flowers of the most important cultivars in the European market, Judia and Longal.…”
Section: Introductionmentioning
confidence: 86%
“…1,2,3,4,6-penta-O-galloyl-β-D-glucose (PGG), a naturally occurring polyphenolic compound abundant in several medicinal plants, was found to exhibit anti-influenza virus activity at non-cytotoxic concentrations. A number of in vitro and in vivo studies have previously shown that PGG exhibits a wide range of biological activities [41], including anti-inflammatory [16], antioxidant [29], anti-angiogenic [25], antitumor [14], antibacterial activity [40], and a broad range of antiviral activity against respiratory syncytial virus (RSV) [39], Hepatitis B virus (HBV) [18] and Herpes simplex virus (HSV) [27][28]31]. Moreover, it has been shown to have an inhibitory effect on viral enzymes such as integrase and reverse transcriptase of human immunodeficiency virus (HIV-1) [1], and NS3 protease of Hepatitis C Virus (HCV) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese galls are used in Chinese medicine to treat coughs, diarrhea, night sweats, dysentery and to stop intestinal and uterine bleeding. The gall of R. chinensis has long been considered to possess many medicinal properties [13].…”
Section: )mentioning
confidence: 99%